Exploring the potential of energy communities in the Italian territory - Brunoro, Silvia; Bizzarri, Giacomo; Boldrin, Enrica (Frontiers in Built Environment, 2024)
Renewable energy communities (RECs) are clean energy, emergent initiatives that invest in people cooperation in order to meet consumption needs and achieve environmental goals. The main aim of the study is to explore the potential of the renewable energy community in Italy by identifying a methodological perspective to describe the development processes and encourage the diffusion of multi-stakeholders’ initiatives across the Italian territory. To do so, we propose a general analysis of the renewable energy community framework, starting with the regulatory and technical–administrative state of the art that regulates renewable energy communities in Italy, based on information from the literature. Then, we interpret the procedure of REC initiatives by systematizing the steps of energy community formation and their characteristics, coming from a literature review of experiences achieved at a national level. Much literature is available on renewable energy technologies, but existing research lacks assessments regarding the description of the formation process of local energy systems applied to realized experiences. To do this, two strategies for the energy community are proposed through a comparative case study analysis to provide a framework for the emerging phenomenon and analyze and define the types of renewable energy communities based on realized experiences in Italy.